Perceived Challenges and Ways to Improve Reading Proficiency for EFL Teachers: Narratives from EFL Teachers - Hakiki, Abid; Mardiana, Rizdika (IJLECR (International Journal of Language Education and Cultural Review), 2024)
The need of using English in global context has led schools in Indonesia to prepare and make their students proficient in English. However, the majority of English teachers may not have attained a level of proficiency deemed necessary for effective teaching. This study aimed to reveal the level of teachers’ reading proficiency and to figure out how they perceived challenges and ways to improve their proficiency. Qualitative data was used as a method of inquiry. The study employed a narrative inquiry to dig deeper into teachers’ perspective. A proficiency test, self-reflection (logbook), and interview were used as the instrument to measure 15 EFL teachers’ proficiency and figure out their challenges and ways to improve their proficiency. The data was analyzed using inductive reflective thematic analysis and the findings showed that teachers proficiency varied, but most of them have a good reading proficiency equal to B2-CEFR level; It is referred to as upper intermediate and independent user by CEFR. In addition, five themes expressing the teachers’ perceived challenges were revealed: 1) They experienced self-errors; 2) The answer is implied; 3) The text is difficult; 4) The question type is unfamiliar; 5) They encountered unfamiliar vocabulary. Moreover, the ways the teachers used to improve their proficiency were: 1) understand the question and passage carefully; 2) find main idea and supporting details; 3) familiarize with the topic; 4) Enrich vocabulary; 5) scan and take notes; 6) predict the question and keep focus. In conclusion, the findings provide the important insights into EFL teachers. Their collective experiences can be used to overcome the challenges faced by EFL teachers.